Is There a Predictive Factor for an Association with Autoimmune Glandular Disease in Children Diagnosed with Celiac Disease? - Fatma İlknur Varol; Emine Çamtosun; Mukadder Ayşe Selimoğlu; Şükrü Güngör (Galenos Yayincilik, 2022)
INTRODUCTION: A close relationship has been suggested between Celiac disease (CD) and glandular autoimmunity. The aim of this study was to determine the predictive factors for autoimmune glandular disease (AGD) in children with CD. METHODS: The study included 228 pediatric patients, diagnosed with CD between 2010 and 2019. The cases with AGD (Group 1) and those without AGD (Group 2) and the patients with type 1 diabetes mellitus (T1DM) (Group A) and those without T1DM (Group B) were retrospectively reviewed and compared in terms of clinical and laboratory features. RESULTS: AGD was detected in 8.8% (n=20) of the patients: T1DM in 13 (65%), T1DM and Hashimoto's thyroiditis (HT) in 3 (15%), HT only in 2 (10%), T1DM and Graves disease (GD) in 1 (5%), and GD only in 1(5%). The mean age at the diagnosis of CD was significantly higher in Group 1 (10.93±4.15 years) compared to Group 2 (8.10±4.19 years) (p<0.05) and also was significantly higher in Group A compared to Group B (p<0.05). Most of the diagnoses of AGD were made before the diagnosis of CD and age was an effective factor. There was no difference between Group 1 and Group 2 and Group A and Group B in terms of gender, typical/atypical CD ratio, tissue transglutaminase IgA (TTGA) level, human leucocyte antigen (HLA)-DQ2 and/or HLA-DQ8 positivity rate, and histopathological stage. DISCUSSION AND CONCLUSION: Although patients with a diagnosis of co-existent CD and AGD were significantly older than patients with isolated CD, gender, celiac symptoms, TTGA level, HLA type, and histopathological stage had no predictive value for the coexistence of AGD in patients with CD.